Novel ultra‐wideband multi‐user receiver for transportation systems communication. Issue 3 (1st September 2014) - Okassa M'foubat, Anicet; Elbahhar, Fouzia; Tatkeu, Charles
Abstract : Ultra‐wideband (UWB) technology can offer very efficient solutions for various vehicular communication applications. The authors propose to use this technique to establish vehicle‐to‐vehicle and vehicle‐to‐infrastructure communications. In fact, compared to traditional carrier‐based technology, UWB is a carrierless system that implements new paradigms in terms of signal generation and reception. Thus, designing a UWB communication system requires the understanding of a mechanism which allows us to have wide bandwidth and very low transmitted powers used jointly to provide a reliable radio link. UWB offers potential transceiver systems with very simple implementations. Two approaches have emerged, which meet all the communication requirements: impulse and multi‐band systems. The present work relies on the first approach. So, the authors propose to use orthogonal functions called modified Gegenbauer functions (MGF) in the UWB system. Different scenarios are studied and compared in the scope of a system offering communication for subway trains. The authors propose a new receiver for the MGF‐UWB communication system. To evaluate the performances of the proposed communication system, the bit error rate values are calculated and analysed in the presence of multi‐user interference, considering synchronous and asynchronous cases. This study shows that this new receiver offers the required performance, for our UWB communication in transport systems, better than the performance obtained using a conventional receiver.